PEMBUATAN KUMPULAN SOAL FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS TARUMANAGARA MENGGUNAKAN ALGORITMA GENETIKA - James Ariel Gunawan; Lely Hiryanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
only refer to the matter of collection questions only. Test Kumpulan also refers to the process of test’s monitoring and storage with related information to make it easier to assembled. Aplikasi Kumpulan Soal Fakultas Teknologi Informasi Universitas Tarumanagara is an application that serves to accommodate the test that would be candidates for inclusion in the test in each course in the Faculty of Information Technology at Tarumanagara University. This application also provides automation features for making the test package. This automation using fuzzy sets and genetic algorithm to produce the prospective questions population of  the test package. Key Words:Kumpulan Soal, Fakultas Teknologi Informasi Universitas Tarumanagara, Fuzzy Sets, algoritma genetika.